2015
DOI: 10.1063/1.4907254
|View full text |Cite
|
Sign up to set email alerts
|

Liquid bulk rotation induced by electric field at free surface

Abstract: In this paper, we induce rotation in a bulk of polar liquid with one free surface, by applying external crossed electric fields. We show that the induced rotation is due to the imposed stresses at the free surface of the liquid. A simple theoretical model was developed based on solving the Navier-Stokes equation that enables us to calculate the average induced stress in the liquid bulk, using experimental measurements of the angular velocity of the liquid. Our results indicate that the induced stresses and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the literature it is reported that polar liquids show macroscopic movement under the influence of an external DC field. [ 40 ] In our experiments, we also observe such macroscopic movement of the NB inside a glass cuvette, when applying a voltage to the electrodes. Here, we term this movement an electrical stirring of the liquid (see Video S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 66%
“…In the literature it is reported that polar liquids show macroscopic movement under the influence of an external DC field. [ 40 ] In our experiments, we also observe such macroscopic movement of the NB inside a glass cuvette, when applying a voltage to the electrodes. Here, we term this movement an electrical stirring of the liquid (see Video S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 66%